2014
DOI: 10.1186/2191-219x-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PET template-based and MRI-based image processing in the quantitative analysis of C11-raclopride PET

Abstract: BackgroundQuantitative measures of 11C-raclopride receptor binding can be used as a correlate of postsynaptic D2 receptor density in the striatum, allowing 11C-raclopride positron emission tomography (PET) to be used for the differentiation of Parkinson’s disease from atypical parkinsonian syndromes. Comparison with reference values is recommended to establish a reliable diagnosis. A PET template specific to raclopride may facilitate direct computation of parametric maps without the need for an additional MR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, MRI images were not available for all participants, thus limiting our capacity to coregister images and determine striatal ROIs. However, we and others have shown that MRI coregistration does not improve quantification of [ 11 C]raclopride binding (Kuhn et al, 2014;Wang et al, 1997). To minimize the acute effects of nicotine on [ 11 C]raclopride binding, smokers were allowed to have a last cigarette 42.5 h before PET scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MRI images were not available for all participants, thus limiting our capacity to coregister images and determine striatal ROIs. However, we and others have shown that MRI coregistration does not improve quantification of [ 11 C]raclopride binding (Kuhn et al, 2014;Wang et al, 1997). To minimize the acute effects of nicotine on [ 11 C]raclopride binding, smokers were allowed to have a last cigarette 42.5 h before PET scanning.…”
Section: Discussionmentioning
confidence: 99%
“…In our implementation, a brain tissue mask is generated based on FreeSurfer segmentation, a CSF dilution factor is calculated for each region, and the raw time activity curve for each region is corrected by this dilution factor before BP ND is calculated. The second method is based on computation of the regional spread function (RSF) (Rousset et al, 2008; Rousset et al, 1998), which has also been extensively applied in PET imaging analysis (Kim et al, 2013; Kuhn et al, 2014; Le Pogam et al, 2011). Our implementation of RSF PVC also included additional ROIs outside the brain (hence, not defined by FreeSurfer) to account for tracer uptake in non-brain tissue.…”
Section: Methodsmentioning
confidence: 99%
“…By standardizing the volumes to be quantified across hemispheres of the brain and across multiple animals, this method generates consistent measurements of decreased tissue glucose uptake. Note that other PET tracers with brain uptake, like 11 C-raclopride for D2 receptors, may be used with this protocol as well 21 . Finally, we describe a method to visualize an ischemic stroke in a rat brain within its skeleton with high anatomical accuracy in three dimensions.…”
Section: Discussionmentioning
confidence: 99%